Stepwise Optimization of the Procedure for Assessment of Circulating Progenitor Cells in Patients with Myocardial Infarction - Cui, Yu-Xin; Johnson, Tom; Baumbach, Andreas; Reeves, Barnaby C.; Rogers, Chris A.; Angelini, Gianni D.; Marsden, Debbie; Madeddu, Paolo (PLOS ONE, 2012)
Background The number and functional activity of circulating progenitor cells (CPCs) is altered in diabetic patients. Furthermore, reduced CPC count has been shown to independently predict cardiovascular events. Validation of CPCs as a biomarker for cardiovascular risk stratification requires rigorous methodology. Before a standard operation protocol (SOP) can be designed for such a trial, a variety of technical issues have to be addressed fundamentally, which include the appropriate type of red blood cell lysis buffer, FMO or isotype controls to identify rare cell populations from background noise, optimal antibody dilutions and conditions of sample storage. We herein propose improvements in critical steps of CPC isolation, antigenic characterization and determination of functional competence for final application in a prospective investigation of CPCs as a biomarker of outcome following acute myocardial infarction. Methods and Findings In this validation study, we refined the standard operating procedure (SOP) for flow cytometry characterisation and functional analysis of CPCs from the first 18 patients of the Progenitor Cell Response after Myocardial Infarction Study (ProMIS). ProMIS aims to verify the prognostic value of CPCs in patients with either ST elevation or non-ST elevation myocardial infarction with or without diabetes mellitus, using cardiac magnetic resonance imaging (MRI) for assessment of ventricular function as a primary endpoint. Results indicate crucial steps for SOP implementation, namely timely cell isolation after sampling, use of appropriate lysis buffer to separate blood cell types and minimize the acquisition events during flow cytometry, adoption of proper fluorophore combination and antibody titration for multiple antigenic detection and introduction of counting beads for precise quantification of functional CPC activity in migration assay. Conclusion and Significance With systematic specification of factors influencing the enumeration of CPC by flow cytometry, the abundance and migration capacity of CPCs can be correctly assessed. Adoption of validated SOP is essential for refined comparison of patients with different comorbidities in the analysis of risk stratification.